HUBUNGAN GAYA KEPEMIMPINAN KONTAK TANI TERHADAP PERSEPSI KINERJA KELOMPOK TANI IKAN LELE DI DESA BABAKAN, CISEENG, KABUPATEN BOGOR - Muhammad Rizqi Mubarok; Wahyu Budi Priatna (Forum Agribisnis, 2016)
The role of Kontak tani in the group is one thing that can`t be separated to the survival of the group. Leadership styles that`s applied by Kontak tani are the ways of working in order to achieve the purpose directing members of a group that can be seen from the performance. This study aims to determine the leadership styles that`s generally applied by Kontak tani and the relationship of leadership styles with performance. The author use validity test, reliability test and Spearman rank test as the analysis tools in this research. Based on the research conducted, leadership styles were commonly applied by the farmer in the village of Babakan contacts are participatory that visible from the involvement of members in the group. In addition, there is a fairly strong correlation between leadership style and performance based on the perception of the group mamber. It needs a through understanding of the various stakeholders within the group or institutional farms that, establishment of groups is based on the increase in well-being and not merely for assistance.